(untitled) (Research, Society and Development, 2021)
This case report is about a 7 year old boy with gastroesophageal reflux disease (GERD) treating since his first years of life. Despite the adequate clinical treatment for this pathology, he occasionally presented with early post-prandial vomits, sometimes requiring hospital internment for hydro electrolyte disorder compensation. After being referred by a General Surgeon, who thought a fundoplication was needed, the patient went to the Dirceu Arcoverde Hospital during a vomiting crisis to be evaluated by a Pediatric Surgeon. The hypothesis of intestinal malrotation associated or not with duodenal web was promptly suggested. The image exams corroborated and Ladd’s surgery was successfully performed. The case report was elaborated through the analysis of medical records of two medical services and reasoned by bibliographic research in the Scielo and Pubmed databases. Our goal with this paper is to bring to memory a differential diagnosis that is rare to a common pathology compatible group of symptoms and highlight the importance of a multidisciplinary team look. If exposed to a patient diagnosed with GERD, associated with growth stop of any kind and refractory clinical treatment, other diagnosis must be made and intestinal malrotation is one of them.